2018
DOI: 10.1002/cyto.b.21643
|View full text |Cite
|
Sign up to set email alerts
|

Accurate quantification of fourteen normal bone marrow cell subsets in infants to the elderly by flow cytometry

Abstract: Background: Studies of normal bone marrow (BM) cell composition by flow cytometry are scarce. Presently, we aimed to quantify 14 cell subsets from infants to elderly patients.Methods: Cell subsets in BM samples from 180 individuals without morphologically abnormal leukocytes were analyzed using a single combination of eight antibodies: CD3/CD10/CD38/CD19/CD36/CD16/CD34/CD45.Results: By comparison with the Holdrinet score, we first validated the immature granulocyte/neutrophil (IGRA/N) ratio as a readily obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 15 publications
(48 reference statements)
1
12
0
12
Order By: Relevance
“…However, hematogones were detected in part of the patients, and their percentages in nucleated cells were remarkably variable. While previous work showed that hematogones were more easily found in infants and adolescents 23 , our study focused on adult ALL patients, which removed the age factor that may significantly affect the level of hematogones.…”
Section: Discussionmentioning
confidence: 99%
“…However, hematogones were detected in part of the patients, and their percentages in nucleated cells were remarkably variable. While previous work showed that hematogones were more easily found in infants and adolescents 23 , our study focused on adult ALL patients, which removed the age factor that may significantly affect the level of hematogones.…”
Section: Discussionmentioning
confidence: 99%
“…В связи с этим необходимо остановиться подробно на особенностях кроветворения детей младшего возраста. Популяционный состав клеток костного мозга новорожденных и детей в возрасте менее 1 года значительно отличается от костного мозга детей более старшего возраста и взрослых [10]. В табл.…”
Section: Discussionunclassified
“…У 3 пациентов определялись различные варианты химерного гена MLL: 46XY?, t(10;11)(p11q23) [14]/46XY [6], t(10:11) MLL/MLLT10 и t(9;11)(p22;q23) MLL-AF9. У 4 пациентов определялся сложный кариотип: 45XY,-7, t(3;3)(q21q26), 48XY,+21,+21, der(17), 53XX,t(1;7)(q21;p15),der(1),+2,+6,+7,+7,der(7)t(1;7),+8,+10, +19 [8]/46,XX [10] и 50,XX,+6,+7,+8, +13, der(11), add(p15), del(17)(q24.). У 1 пациента цитогенетические аномалии не выявлены: 46XY.…”
Section: материалы и методыunclassified
See 1 more Smart Citation
“…Delineation of normal/activated state and identification of abnormal populations is critical (7). Such constantly growing polychromatic assay protocols require realigned baseline assays different from the more traditional 3-4 color MAb combinations (2,(8)(9)(10)(11).…”
mentioning
confidence: 99%